2008
DOI: 10.1002/qua.21875
|View full text |Cite
|
Sign up to set email alerts
|

Inactivation of [FeFe]‐hydrogenase by O2. Thermodynamics and frontier molecular orbitals analyses

Abstract: The oxidation of H-cluster in gas phase, and in aqueous enzyme phase, has been investigated by means of quantum mechanics (QM) and combined quantum mechanics-molecular mechanics (QM/MM). Several potential reaction pathways (in the above mentioned chemical environments) have been studied, wherein only the aqueous enzyme phase has been found to lead to an inhibited hydroxylated cluster. Specifically, the inhibitory process occurs at the distal iron (Fed) of the catalytic H-cluster (which is also the atom involve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
20
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 16 publications
(21 citation statements)
references
References 58 publications
1
20
0
Order By: Relevance
“…). It has been shown by theoretical prediction and experiment that Fe d is most likely the place of catalysis and plays a crucial role in O 2 ‐induced inhibition . In fact, coordination of O 2 to Fe d (see Fig.…”
Section: Proof Of Principle: Mutant Screening In Hydrogenasementioning
confidence: 93%
“…). It has been shown by theoretical prediction and experiment that Fe d is most likely the place of catalysis and plays a crucial role in O 2 ‐induced inhibition . In fact, coordination of O 2 to Fe d (see Fig.…”
Section: Proof Of Principle: Mutant Screening In Hydrogenasementioning
confidence: 93%
“…The inactivation kinetics was first studied using PFV under numerous conditions with varying [O 2 ], [H 2 ], and/or redox potential (Goldet et al, ; Stripp et al, ; Vincent et al, ). The earlier work (Baffert et al, ; Dogaru, Motiu, & Gogonea, ; Goldet et al, ; Goris et al, ; Lambertz et al, ; Lautier et al, ; Stripp et al, ; Vincent et al, ) showed that [NiFe] and [FeFe] hydrogenases undergo inactivation at significantly different rates (Table ), which also go through unequal intermediate states (Figure a). The half‐life of the former in the air‐saturated buffer is in the order of tens of minutes while it is in the order of tens of seconds for the latter.…”
Section: O2 Inactivation and Protection Mechanismmentioning
confidence: 95%
“…Infrared (IR) spectroscopy confirmed the formation of the O 2 ‐bound state within few hundreds of milliseconds (Bingham, ) while the degradation proceeded in the order of minutes (Bingham et al, ; Goldet et al, ; Koo & Swartz, ; Koo et al, ; Lambertz et al, ; Lautier et al, ; Orain et al, ; Swanson et al, ). A series of reactions are suspected to be involved in the degradation (Dogaru et al, ; Finkelmann, Stiebritz, & Reiher, ; Hong & Pachter, ; Kubas et al, ; Lambertz et al, ; Stiebritz & Reiher, ), with the end product being the hydrogenase lacking the 2Fe subcluster in the active site. Notably, the end product of the O 2 ‐driven [FeFe] hydrogenase inactivation is able to restore the enzymatic activity when incubated in vitro with maturation machinery, namely HydE, F, and G (Swanson et al, ).…”
Section: O2 Inactivation and Protection Mechanismmentioning
confidence: 99%
“…Previous density functional theory (DFT) as well as hybrid quantum mechanics/molecular mechanics (QM/MM) calculations 1, 17–23 have been successful in clarifying some aspects of the catalytic properties of the H‐cluster. As in previous computational studies 1, 18, CH 3 S is substituted for cysteine, and a H + replaces the proximal cubane.…”
Section: Introductionmentioning
confidence: 99%